Obstetrics normal and problem pregnancies - Gabbe, Steven G.; Niebyl, Jennifer R.; Simpson, Joe Leigh 1943-; Landon, Mark B. (Elsevier/Saunders, 2012)
Highly readable, well illustrated, and easy to understand, Obstetrics: Normal and Problem Pregnancies remains your go-to choice for authoritative guidance on managing today's obstetric patient. Reflecting the expertise of internationally recognized authorities, this bestselling obstetrics reference has been thoroughly revised to bring you up to date on everything from ultrasound assessment of fetal anatomy and growth, to medical complications in pregnancy, to fetal therapy...and much more!It's the place to turn for the up-to-date, dependable answers you need to overcome the technical challenges you face every day.